A baseline study on elemental concentration and potential ecological risk status of the surface sediments of Ashtamudi Lake, south west coast of India. (September 2020) - Hussain, S.M.; Anbalagan, S.; Kumar, K. Suresh; Neelavannan, K.; Pradhap, D.; Radhakrishnan, K.; Godson, Prince S.; Krishnakumar, S.
Abstract: Element concentration (Fe, Mn, Pb, Zn, Cu, Cr, Ni and Co) in the surface sediments of Ashtamudi estuary, Southwest coast of India, has been analyzed to understand the spatial variation and potential ecological risk status. The sediment pollution index and Potential Ecological Risk index suggest that the northeastern part of the estuary exhibits low to moderate polluted sediments with moderate ecological risk. The results of correlation analysis indicate that the natural weathering process and river input play an important role in the distribution of the elements in the surface sediments of the estuary. The extracted factor results indicate that the fine sediment fractions supporting for accumulation of the trace elements, whereas the enriched level of Fe and Mn is chiefly controlled by the riverine process, and other elements are contributed by anthropogenic influences.